Nollywood : the making of a film empire - Witt, Emily, 1981- (New York, NY : Columbia Global Reports, 2017)
"How did Nigeria create the second largest movie industry in the world? Nollywood began in Nigeria in the 1990s and has grown into the second largest film industry in the world in the number of films produced annually, behind only Bollywood and ahead of Hollywood. Reporter Emily Witt travels to Nigeria to offer a vivid, rollicking tour of the industry today. She meets with young filmmakers and actors trying to break into the industry, covers start-ups trying to digitalize what has been largely an economy based on piracy, and documents the shooting of a historic epic in the northern city of Jos, which is emerging after years of civil conflict and a brutal attack by Boko Haram. The Nigerian movie industry, like Nigeria itself, is an organized chaos, but amid electricity cuts, fuel scarcity, and countless other obstacles its producers are pursuing the very real possibility that Nigerian movies could become a global brand as recognizable as the Bollywood musical, the Hong Kong kung fu flick, or the Hollywood blockbuster."--Page 4 of cover.
Prologue -- Film synopsis : Living in Bondage -- A premiere -- Film synopsis : Violated -- A visit to a set in Jos -- Film synopsis : 30 Days in Atlanta -- Pirates and traders -- Film synopsis : Taxi Driver (Oko Ashewo) -- Digital futures -- Film synopsis : Ojuju -- Asaba -- Film synopsis : Nkoli Nwa Nsukka -- Conclusion.
Includes bibliographical references (pages 119-123).
Print version record.
JSTOR
Keywords: Motion picture industry -- Nigeria -- History; Motion pictures -- Nigeria -- History and criticism; Motion pictures -- Plots, themes, etc; Cinéma -- Industrie -- Nigeria -- Histoire; Cinéma -- Nigeria -- Histoire et critique; Cinéma -- Intrigues, thèmes, etc; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- General; Motion picture industry; Motion pictures; Motion pictures -- Plots, themes, etc; Nigeria; Criticism, interpretation, etc; History; Electronic books